Teacher Professionalism: Effects of AI Literacy, Coaching, and Motivation in Islamic Schools - Noor Lailie; Kaniati Amalia; Mohammad Syahidul Haq; Amrozi Khamidi; Syunu Trihantoyo; Andi Kristanto (Bulletin of Educational Management and Innovation, 2025)
Background: The rapid transformation of education in the Society 5.0 era requires teachers to integrate Artificial Intelligence (AI) into pedagogical practices while maintaining professional and ethical standards. In Mojokerto’s Integrated Islamic Elementary Schools (SDIT), teachers face challenges such as digital anxiety, administrative burdens, and limited managerial support, which hinder their ability to adapt to AI-driven learning environments. Purpose: This study investigates the influence of AI literacy, coaching, and work motivation on teacher professionalism in SDIT schools across Mojokerto, both individually and collectively Method: Employing a quantitative causal design, the research involved 114 SDIT teachers selected through total sampling. Data were collected using validated Likert-scale questionnaires and analyzed with multiple linear regression via SPSS, supported by classical assumption tests to ensure model reliability. Findings: Results demonstrate that AI literacy, coaching, and work motivation significantly and simultaneously affect teacher professionalism (F-value = 28.452; Sig < 0.001). Among these, work motivation emerged as the most dominant predictor. The findings underscore the necessity of a holistic approach that combines technological proficiency, managerial empowerment through coaching, and psychological reinforcement via motivation to enhance teacher professionalism in Islamic elementary education.